Research on Resource Allocation Algorithm of Smart Grid based on 5G Network Slicing Technology - Jialin, Luo; Yao, Xie; Kangping, Yang; Ziqi, Zhou; Xinhui, Zhong (2022 IEEE 4th International Conference on Power, Intelligent Computing and Systems (ICPICS), 2022)
Based on the development status of 5G technology and smart grid and the future demand of power service terminals, this paper uses network slicing technology and utility maximization algorithm to realize the dynamic allocation of limited resources in smart grid, which meets the requirements of user experience quality and service quality, conforms to the evolution route of 5G technology and the development direction of smart grid system, and provides a reference scheme for the allocation of network slicing resources in smart grid.